Successful outcome of modified Shirodkar cerclage in a patient with a history of failed vaginal cerclage: A case report - Bharti, Soni; korde, Pooja; Vatsa, Richa; Sharma, K Aparna (Indian Journal of Case Reports, 2025)
Cervical insufficiency is an important cause of bad obstetrics history and is preventable. McDonald’s cervical cerclage has been used in obstetrics for a long era to prevent pre-term births. However, there are cases of failed cervical cerclages and then the dilemma arises whether to opt for another vaginal cerclage or a transabdominal cerclage. Each route of cerclage has its own advantages as well as shortcomings, making decisions difficult for clinicians as well as patients. We present the case of a 22-year-old female with previously failed McDonald cervical cerclage who opted for modified Shirodkar cerclage and had a good outcome. This case highlights the benefit of modified Shirodkar cerclage in cases of previously failed cervical cerclages.